Circulating current suppression in modular multilevel converters with even-harmonic repetitive control - Yang, Shunfeng (2019)
Due to voltage mismatch between phase legs and the dc bus in modular multilevel converters (MMCs), the differential current in MMCs is inherently subjected to circulating even-order harmonics. Repetitive control based active harmonic suppression methods can be adopted to eliminate such harmonics. Nevertheless, conventional repetitive controllers have a relatively slow dynamic response, because all the sampled errors in the past one cycle have to be stored, which causes a response delay for one fundamental period. This paper proposes an improved repetitive control scheme that exclusively copes with even-order harmonics based on the circulating current characteristics of MMC systems. The design details of the even harmonic repetitive control scheme according to the harmonics characteristics are provided. The proposed even-harmonic repetitive control scheme requires halved data memory to store error samplings and the delay introduced by the repetitive controller is also reduced. According to the frequency domain analysis, the even-harmonic repetitive control features faster convergence rate, greater low-frequency gains, higher crossover frequency, and higher tolerance against system frequency deviation, while possessing the same even-order harmonics suppression capability and stability as conventional ones. Simulation and experimental results are presented to show the steady-state harmonics suppression capability, dynamic response, and disturbance tolerance of the proposed even-harmonic repetitive control scheme.